Morphometric evaluation of occipital condyles for a safe transcondylar approach through skull base - Vijisha Phalgunan; Suresh Narayanan (Wolters Kluwer Medknow Publications, 2018)
Aims and Objectives: Occipital condyle is an important landmark in transcondylar approach for surgery of lesions ventral to the brainstem, hence it is imperative to understand the anatomical aspects of occipital condyle. The aim of the present study is to analyse the morphometrical aspects of occipital condyle and to highlight its importance in surgical resection. Materials and method: Hundred occipital condyles of fifty dry skulls were used for this study. Twenty-six parameters were measured. The measurements were made separately for right and left sides. Results: The mean length of occipital condyle was found to be 22.92mm. The distance between the intracranial orifice of the hypoglossal canal and the posterior margin of occipital condyle was 12.55±0.05mm.The commonest location of intracranial orifice and extracranial orifice of hypoglossal canal was found to be at location 3 and location 2 respectively. Occipital condyle was oval in most skulls. Conclusion: Occipital condyle can be safely drilled for a distance of 12 mm from the posterior margin before encountering the hypoglossal canal. Surgeons operating in this area must consider the variations of parameters of south Indian skulls.